Will German banks earn their cost of capital? - Andreas Dombret; Yalin Gündüz; Jörg Rocholl (Deutsche Bundesbank, 2017)
In recent years, the German banking sector has overcome major challenges such as the global financial crisis and the European debt crisis. This paper analyses a recent development as a particular determinant of the future outlook for the German banking sector. Interest rates are at historically low levels and may remain at these levels for a considerable period of time. Such levels pose a specific challenge to banks which are heavily dependent on interest income, as is the case for most German banks. We consider different interest rate scenarios and analyse the extent to which they cause a further narrowing of the interest rate margin. Our results indicate that a projected decline in this margin will result in no more than 20% of German banks earning a cost of capital of 8% by the end of this decade. This decline is somewhat alleviated by the fact that German banks can apply a special feature of German accounting standards by using hidden and open reserves.
Keywords: G21; G28; 330; German banking sector; low interest period; profitability; hidden and open reserves